2012
DOI: 10.1037/a0030192
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons make errors as a result of interval timing in a visual, but not a visual-spatial, midsession reversal task.

Abstract: It has been shown previously that pigeons make surprising errors on a visually based midsession reversal task (Cook & Rosen, 2010; Rayburn-Reeves, Molet, & Zentall, 2011). We trained birds with red and green sidekeys, with one color rewarded in the first 40 trials (S1) and the other color rewarded in the latter 40 trials (S2). Importantly, in Phases 1 and 3, red and green were always presented on the same side, whereas in Phase 2 sidekeys were presented on the left and right equally often. In Phases 2 and 3, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 25 publications
7
68
0
Order By: Relevance
“…This account, then, ostensibly pits two competing sources of information against each other: external feedback from the previous trial, and intrinsic temporal cues. Indeed, some evidence that memory for the preceding response may be involved is suggested by the fact that pigeons' performance increases when both spatial and visual information are relevant (McMillan et al, 2014;McMillan & Roberts, 2012). If this is the case, then the results from the present experiment showing differences between pigeons and rats may be due to differences in memory for preceding events and/or differences in the salience of temporal cues.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This account, then, ostensibly pits two competing sources of information against each other: external feedback from the previous trial, and intrinsic temporal cues. Indeed, some evidence that memory for the preceding response may be involved is suggested by the fact that pigeons' performance increases when both spatial and visual information are relevant (McMillan et al, 2014;McMillan & Roberts, 2012). If this is the case, then the results from the present experiment showing differences between pigeons and rats may be due to differences in memory for preceding events and/or differences in the salience of temporal cues.…”
Section: Discussionmentioning
confidence: 53%
“…Since then, strong evidence has been found that pigeons do appear to use the passage of time as a cue to reverse (McMillan & Roberts, 2012, 2015. The use of time as a cue for reversing is not optimal, however, because judgments of time into the session provide a less accurate cue than the outcome of the preceding trial.…”
mentioning
confidence: 99%
“…Further support for the use of a timing cue in MSR was also provided by McMillan and Roberts (2012). They trained pigeons on a simple discrimination using red and green stimuli with a 6.0 s inter-trial interval (ITI) between each trial.…”
Section: Control Of Switching Behavior In Mid-session Reversalmentioning
confidence: 99%
“…McMillan and Roberts (2012), for example, trained pigeons on an MSR task using a combination of relevant visual and spatial information. Across three phases, pigeons first experienced discriminations in which both spatial and visual cues were relevant (Phase 1), then only visual cues were relevant (Phase 2), and finally back to both cues being relevant (Phase 3).…”
Section: Control Of Switching Behavior By Reinforcement Cuesmentioning
confidence: 99%
“…Additionally, these results are precisely what one should expect given the literature regarding midsession reversals in pigeons. Similarly to choice behavior, variability in performance is controlled precisely by reinforcement probabilities when these probabilities are unambiguously indicated by a discrete, salient visual cue (but see McMillan & Roberts, 2012).…”
Section: Discussionmentioning
confidence: 99%